Effects of oral of administration of monoglycide laurate on virus load and inflammation in PEDV infected porcine - Liu, Zheyan; Zhu, Ling; Zhao, Xiaonan; Liu, Jian; Cheng, Huangzuo; Zhang, Lina; Tang, Huaqiao; Sun, Xiangang; Hu, Youjun; Xu, Zhiwen (Frontiers in Veterinary Science, 2022)
To investigate the effect of monoglyceryl laurate (GML) against PEDV in vivo, the clinical signs, pathological changes, tissue viral load and cytokine levels of piglets were compared in different GML treatment groups and PEDV infected group. The diets of experimental groups were supplemented with different doses of GML (5g for A1, 10g for A2, 20g for A3) on day 1, 2, and 3 after PEDV challenge, and the virus challenge group (group C) and blank group (group B) were set as control. The results showed that compared with group C, groups As could reduce the mortality rate of piglets, among which the protection rates of groups A2 and A3 could reach 100%. The trend of weight loss of piglets was effectively slowed down and growth performance recovered in GML treated groups. GML reduced the pathological damage of intestinal tract and the viral load in intestine and mesenteric lymph nodes. The levels of IL-8 and TNF-α in the blood of group As were inhibited by GML in a dose-dependent manner when compared with group C. Our study suggests that GML has potential anti-PEDV effects in vivo.